Iodine supplementation for pregnancy in Portugal: identification of nutritional composition of iodine containing supplements and characterization of pharmacy dispenses from 2008-2022 - Machado, Sarai Isabel; Roque, Susana; Lopes-Pereira, Maria; Costeira, Maria José; Costa, Patrício; Borges, Nuno; Pereira, Ruben; Mendes, Zilda; Rodrigues, António Teixeira; Palha, Joana Almeida (Frontiers in Endocrinology, 2025)
BackgroundIodine is essential for the proper development of the central nervous system. In Portugal, despite of self-reports of iodine supplements intake by pregnant women, iodine deficiency still prevails. This study intended to characterize the pharmacy sales of iodine-containing supplements and their use by women in Portugal.MethodsData from all available supplements with indication for use in the prenatal time, for the period 2008-2022, was obtained from the Portuguese Association of Pharmacies. To infer from the use of iodine supplements by women during preconception, pregnancy and lactation, pharmacy dispenses, between 2019 and 2021, were collected from a sample of female consumers, identified with at least one prescription of iodine-containing supplements.ResultsEighty-eight per cent of the iodine-containing supplements state the recommended iodine concentration. The annual sales increased continuously, reaching an estimated of 109 µg per day in 2022. Estimated mean duration of supplementation to women prescribed with iodine-containing supplements for preconception/pregnancy/lactation was of 4.5 months (SD = 3.8) and less than 1% of women was covered for the advisable period of 18 months.ConclusionThe estimated duration of iodine supplementation to women during preconception, pregnancy and lactation is below recommendations. Additional public health measures, such as universal salt iodization and literacy campaigns are needed to ensure iodine sufficiency to women and their developing fetus.